ORTHOMETRIC HEIGHT DETERMINATION IN JAKARTA AND SUNDA STRAIT AREA USING THE GEOPOTENTIAL NUMBER APPROACH - Sarsito, Dina Anggreni; Bramanto, Brian; Andreas, Heri; Pradipta, Dhota; Triwibowo, Sidiq (Bulletin of Geology, 2024)
Orthometric height is a physical height type used by Indonesia in local/national reference systems for determining positions used in various scientific and engineering activities. The main constraint in determining orthometric height is that it is theoretically difficult to realize that gravity measurements must be carried out along the plumb lines that connect the topographic equipotential surface with the geoid surface. Another constraint is that it requires precise physical height difference measurementsfrom tie points, which are usually located in coastal areas, to locations on land that are far from the coast. This research examines the possibility of determining orthometric physical height at several GNSS stations in the Jakarta and Sunda Strait areasusing the geopotential number approach as an alternative solution to the difficulties caused by the aforementioned constraints. The first type of orthometric height obtained from GNSS geodetic height observations with geoid undulation obtained from the EGM2008 global gravity model is then used as a comparison for the second type of orthometric height obtained from the geopotential number approach. The pattern of geopotential numbers on the islands of Java and Sumatra has the same pattern, namely that the value increases as the topographic elevation increases. This phenomenon is in line with the terrestrial survey approach carried outso far, that the meansea level can be assumed to be an estimate of the geoid surface, which is used as a reference for the gravity potential surface. The average difference in height between the two types of orthometric height is 0.39 meters, with a difference interval between -1.80 meters and 2.73 meters. The results obtained show that the geopotential number approach can be used as an alternative for determining orthometric height if direct gravity measurements and/or precise physical height difference measurements cannot be carried out in the monitoring area. Key words: Orthometric, Geopotential Number, Geoid, Jakarta, Sunda Strait.